Supply Chain Risk Management: A Review - Gurdeep Singh; Nabsiah Abdul Wahid (International Journal of Supply Chain Management, 2014)
Many different entities are responsible for or reliant upon the functioning of the global supply chain, including regulators, law enforcement, public-sector buyers, private-sector businesses, and other foreign and domestic partners; mainly because the global supply chain provides the food, medicine, energy, and products that support our way of life. To do this, the global system relies upon an interconnected web of transportation infrastructure and pathways, information technology, and cyber and energy networks. While these interdependencies promote economic activity, they also serve to propagate risk across a wide geographic area or industry that arises from a local or regional disruption. This paper aims to introduce the concept and framework of supply chain risk management (SCRM) by reviewing the literature. The review emphasises on the definition of each component within SCRM followed by the integration of the components into one of the current models applied by the global supply chain industry.